A new apparatus for the study of pullout behaviour of soil-geosynthetic interfaces under sustained load over time. Issue 6 (December 2021) - Cardile, G.; Pisano, M.; Recalcati, P.; Moraci, N.
Abstract: At present, the design of geosynthetic-reinforced soil structures is executed with reference to the tensile strength of the reinforcement obtained from in-air short-term tensile tests, decreasing this value by means of several factors. Among these, the creep effect resulting from in-air tensile creep tests reduces tensile strength the most. Consequently, this procedure does not take into account the effects of soil confinement and interaction on the tensile response of the reinforcements. This paper illustrates a new large-scale pullout prototype apparatus, with the capacity to investigate the behaviour of a geosynthetic reinforcement embedded in a compacted soil and subject to a tensile load kept constant over time. The apparatus allows the verification of how the soil can modify the prediction of the long-term behaviour of geosynthetics. Results in terms of confined tensile strains were analysed, and the comparison of those values with the strains obtained by in-air tensile creep tests has led to the conclusion that the creep reduction factor might be conservative. Moreover, the confined tensile strains were related to the apparent coefficients of friction to propose a new procedure capable of determining the design interaction parameter under long-term pullout load as a function of the allowable reinforcement strains.